The Contribution Of Paramedics To The Management Of Heat Stroke And Heat Exhaustion (The Review of Diabetic Studies, 2025)
Heat-related emergencies, particularly heat exhaustion and heat stroke, have become increasingly prevalent worldwide due to climate change effects. Paramedics play a crucial role in the early recognition and management of these conditions, significantly influencing patient outcomes. This review comprehensively examines the contribution of paramedics to the management of heat-related emergencies, focusing on the pathophysiological understanding, importance of prehospital recognition and intervention protocols, and impact on morbidity and mortality mitigation. The epidemiology reveals rising incidence and mortality rates globally, with certain populations at higher risk. Pathophysiologically, heat exhaustion and heat stroke represent a spectrum of severity distinguished by the degree of hyperthermia and organ dysfunction. Cellular and systemic responses, including endothelial injury, cytokine storms, and coagulopathy, contribute to multiorgan failure. Paramedics employ field assessment tools, vital signs interpretation, and thorough scene evaluation to differentiate heat exhaustion from heat stroke. Prehospital management strategies prioritize airway, breathing, and circulation support, rapid cooling techniques, circulatory and renal support, neurological monitoring, and timely transportation decisions. Special considerations are necessary for pediatric and geriatric populations due to their physiological vulnerabilities. Technological innovations, such as wearable sensors and telemedicine, enhance paramedics' assessment and intervention capabilities. However, challenges persist in resource-limited settings, delayed recognition, and mass-casualty events. Addressing these limitations through enhanced training, resource allocation, and ethical decision-making frameworks is crucial for improving prehospital care in heat-related emergencies.